Eugène Bouchut's (1818–1891) Early Anticipation of the Concept of Brain Death. Issue 3 (26th July 2022) - Saad, Toni
Abstract: The conventional historical account of the concept of brain death credits developments and discoveries of the twentieth century with its inception, emphasizing the role of technological developments and professional conferences, notably the 1968 Ad Hoc Committee of the Harvard Medical School to Examine the Definition of Brain Death. This essay argues that the French physician Eugène Bouchut anticipated the concept of brain death as early as 1846. Correspondence with Bouchut's understanding of brain death and one important contemporary concept of brain death is established then contrasted with current trends of defining death as the death of the brain. The philosophical factors that influenced Bouchut and the later developments of concepts of brain death are considered, with special reference to mechanistic philosophy and vitalism.